Exploration of Students' Perceptions of The Role of Family in Academic Achievement - Wildan Hakim Siregar; Viola Eninta; Mita Raisa; Riski Saputra; Musbar Habibi (Madiha Press, 2026)
This research uses a descriptive qualitative approach. This research explores students' perceptions of the role of family in academic achievement, with a focus on the dynamics between perceived support and stress. Through a qualitative approach, data is collected from in-depth interviews with students from various backgrounds. The research results show that family support, in the form of moral encouragement and financial assistance, greatly influences students' academic motivation. However, in certain situations, such as high expectations or comparisons with siblings, this support can turn into stressful pressure. College students often feel caught between the desire to meet family expectations and the need to pursue their personal goals. This research also identified that the role of the family not only impacts motivation, but also the mental health of students. By understanding the complexity of this relationship, it is hoped that it can provide insight for parents and educators in creating a supportive environment without causing excessive pressure. It is hoped that these findings can become a reference in developing more effective intervention strategies to support students' academic well-being.